Comparison of methods for constructing joint confidence bands for impulse response functions - Helmut Lütkepohl; Anna Staszewska-Bystrova; Peter Winker (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
In vector autoregressive analysis confidence intervals for individual impulse responses are typically reported to indicate the sampling uncertainty in the estimation results. A range of methods are reviewed and a new proposal is made for constructing joint confidence bands, given a prespecified coverage level, for the impulse responses at all horizons considered simultaneously. The methods are compared in a simulation experiment and recommendations for empirical work are provided.
Keywords: C32; 330; vector autoregressive process; impulse responses; bootstrap; confidence band